2013
DOI: 10.1186/1742-4690-10-100
|View full text |Cite
|
Sign up to set email alerts
|

Ability of HIV-1 Nef to downregulate CD4 and HLA class I differs among viral subtypes

Abstract: BackgroundThe highly genetically diverse HIV-1 group M subtypes may differ in their biological properties. Nef is an important mediator of viral pathogenicity; however, to date, a comprehensive inter-subtype comparison of Nef in vitro function has not been undertaken. Here, we investigate two of Nef’s most well-characterized activities, CD4 and HLA class I downregulation, for clones obtained from 360 chronic patients infected with HIV-1 subtypes A, B, C or D.ResultsSingle HIV-1 plasma RNA Nef clones were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
129
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(147 citation statements)
references
References 64 publications
17
129
1
Order By: Relevance
“…As expected for samples obtained during early infection following peak viremia, pVL correlated inversely with the estimated number of days postinfection in both AC (Spearman R ϭ Ϫ0.77, P ϭ 0.01) and AP (R ϭ Ϫ0.38, P ϭ 0.007). Consistent with previous observations in other cohorts (21,56,57), Nef CD4 and HLA class I downregulation functions correlated positively in both AC (R ϭ 0.74, P ϭ 0.02) and AP (R ϭ 0.56, P Ͻ 0.001). Given that these activities are largely genetically separable in mutational studies of HIV-1 reference strains (58,59), this result supports the idea of the existence of secondary genetic determinants lying outside critical motifs in patient-derived Nef isolates that may modulate function and/or protein stability.…”
Section: Isolation Of Early Nef Clones From Hiv-1 Controllers and Prosupporting
confidence: 80%
See 2 more Smart Citations
“…As expected for samples obtained during early infection following peak viremia, pVL correlated inversely with the estimated number of days postinfection in both AC (Spearman R ϭ Ϫ0.77, P ϭ 0.01) and AP (R ϭ Ϫ0.38, P ϭ 0.007). Consistent with previous observations in other cohorts (21,56,57), Nef CD4 and HLA class I downregulation functions correlated positively in both AC (R ϭ 0.74, P ϭ 0.02) and AP (R ϭ 0.56, P Ͻ 0.001). Given that these activities are largely genetically separable in mutational studies of HIV-1 reference strains (58,59), this result supports the idea of the existence of secondary genetic determinants lying outside critical motifs in patient-derived Nef isolates that may modulate function and/or protein stability.…”
Section: Isolation Of Early Nef Clones From Hiv-1 Controllers and Prosupporting
confidence: 80%
“…Similarly, it has been reported that the effects of Nef on host HLA expression may differ between HLA alleles (82). While we assessed only downregulation of HLA-A*02 here, a previous study by our group observed a strong correlation between the abilities of patient-derived Nef clones to downregulate A*02 and B*07 in this same assay system (56). Changes in Nef function between baseline and follow-up clones sampled were observed up to 516 days later.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance of HIV-mediated CD4 down-modulation for the viral replication and the disease progression [2][3][4]20] renders research on this topic of vital importance to better understand the virus and to identify host factors involved in the process. We were especially interested in exploring the cellular pathways that are exploited by the virus to achieve CD4 down-modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus type 1 (HIV-1)-induced CD4 downregulation is an important determinant of viral replication in vivo (Ali et al, 2009;Argañaraz et al, 2003;Carl et al, 2001;Casartelli et al, 2003;Mann et al, 2013Mann et al, , 2014Watkins et al, 2013) and for years it has been proposed as an interesting target for the research of new antiviral therapeutic strategies. Cellular co-factors of HIV could have great potential in the future of anti-retroviral therapy (Arhel & Kirchhoff, 2010;Tintori et al, 2014); therefore it is important to completely elucidate the CD4 downregulation pathway in order to find possible co-factors involved in the process.…”
Section: Introductionmentioning
confidence: 99%